Web-Enabled Business in SMEs in Less Developed Regions: An Empirical Study of the Influence of Government Incentives, Physical Location and Cost. Issue 25 (2019) - Aliu, Albert; Stapleton, Larry; Metin, Hasan; Hajrizi, Edmond
Abstract: Digitally-enabled automated business solutions have the capacity to transform the economies of less developed regions. Indeed, the penetration of web-enabled automated business systems amongst small firms in less developed regions is a good indicator of the health of an emerging digitally-enabled economy. These technologies open up new markets and, through the effective control of supply chain logistics, create new efficiencies which enable these firms to compete. This research explores current e-readiness trends concerning small to medium size enterprises in the Western Balkan region, a region under-represented in the recent literature. It focuses attention on three main factors which appear in the literature: government incentives, physical location and cost. The study concludes that the role of the emerging technologies and the Internet is reshaping the business model of the enterprises in the region and draws conclusion about important influencing factors.